Exploring participation experiences of youth who use AAC in social media settings: impact of an e-mentoring intervention. (3rd April 2019) - Grace, Emma; Raghavendra, Parimala; McMillan, Julie M.; Gunson, Jessica Shipman
Abstract: The contribution of cross-age peer e-mentoring on reported experiences of participation during online conversations using social media was explored in this pre-experimental study. Young people ( n  = 4, aged 13; 4–18;3 [years; months]) who used augmentative and alternative communication (AAC) participated in an e-mentoring intervention. Two mentors who also used AAC had regular conversations with the participants via Facebook 1, email, or Skype 2 . It was predicted that the mentoring support would contribute to experiences of participation in online conversations outside of the e-mentoring intervention. Reported experiences of participation in online conversations with communication partners other than the mentor were measured at four time points. The Self-Reported Experiences of Activity Settings was used for this purpose because it consists of five domains: Personal Growth, Psychological Engagement, Social Belonging, Meaningful Interactions, and Choice and Control. These domains are associated with the construct of involvement in activity settings. Results showed varied scores between participants and across the domains. Reported experiences of choice and control increased slightly across time. Despite some variation in self-ratings, the participants reported experiencing choice and control, psychological engagement, and social belonging in online conversations. There is need for more research in this emerging area.